THE IMPORTANCE OF TAX PAYMENTS IN THE DEVELOPMENT OF SMALL BUSINESS - Axrorov Abbos Aslamjon o’g’li; Salimova Sevinch Bekzod qizi; Aliqulov Musurmon Kamoliddin o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article provides a comprehensive analysis of the economic importance of tax payments in the development of small business. In particular, the impact of tax policy on the activities of small business entities, as well as its role in increasing their financial stability and investment attractiveness, is scientifically substantiated. As of 2026, in many countries, including Uzbekistan, mechanisms such as optimizing the tax burden, granting benefits, and introducing simplified tax systems are widely applied in order to stimulate economic growth and support small business. The article also notes that in 2026, the share of small business in GDP in many developing countries is around 50–60%, while in Uzbekistan this indicator has approached 55%. This indicates the need for further improvement of tax policy. In conclusion, it is substantiated that effective tax mechanisms are an important factor in the development of small business.